Innovación abierta: una revisión sistemática de la literatura - Portocarrero García, Milagros Sara; Timaná, Juan S. (Universidad de Cienfuegos, 2023)
Open innovation is a new way of managing innovation. The purpose of this article is to explore and investigate the importance of open innovation, the understanding and evolution in the application by companies. A literature review was carried out in the Web of Science, Scopus and Proquest databases. This literature review process shows that open innovation is valuable for companies to use it. Apply, has an important place in innovation management, and can be applied not only by large companies, but also in small and medium-sized companies. Perspectives of the concept of Open Innovation from various authors are presented, and although the purpose is to use internal and external resources for the creation of new products, it is necessary to mention that innovation is essential for business growth and development.

La Innovación Abierta es una nueva forma de gestionar la innovación. El presente artículo tiene por propósito explorar e investigar sobre la importancia de Innovación Abierta, la comprensión y evolución en la aplicación de parte de las empresas. Se llevó a cabo una revisión de la literatura en las bases de datos de Web of Science, Scopus y Proquest. Este proceso de revisión de literatura muestra que la Innovación Abierta es valiosa para que las empresas la apliquen, tiene un importante lugar en la gestión de la innovación, pudiendo aplicarse no solamente por grandes empresas, sino también en pequeñas y medianas empresas. Se presentan perspectivas del concepto de Innovación Abierta de diversos autores, y aunque el fin es utilizar recursos internos y externos para la creación de nuevos productos, es necesario mencionar que la innovación es fundamental para el crecimiento y el desarrollo empresarial.
Keywords: Literature review; Open innovation; Revisión de literatura; Innovación Abierta; Innovation Management; Gestión de la innovación; https://purl.org/pe-repo/ocde/ford#5.02.04